Respostas
respondido por:
5
-> Lembrando que cosseno varia de -1 a +1
cos(x) = 3m - 2
-1 ≤ cos(x) ≤ +1
-1 ≤ 3m - 2 ≤ +1
+1 ≤ 3m ≤ +3
+1/3 ≤ m ≤ +1
-> Logo os valores que satisfazem a equação são [ +1/3 , +1 ]
cos(x) = 3m - 2
-1 ≤ cos(x) ≤ +1
-1 ≤ 3m - 2 ≤ +1
+1 ≤ 3m ≤ +3
+1/3 ≤ m ≤ +1
-> Logo os valores que satisfazem a equação são [ +1/3 , +1 ]
alinecris189:
muito obrigada
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás